SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARWAYAN MENGGUNAKAN METODE MULTIFACTOR EVALUATION PROCESS PADA PT. KONSUIL WILAYAH SULAWESI TENGGARA - Subhan Akbar Diwanda; Isnawaty Isnawaty; La Ode Hasnuddin S. Sagala (semanTIK, 2016)
PT. Konsuil Region Southeast Sulawesi in determining the performaseveral factors ratings. The assessment factors consist of prowess, charactFor the sake of the effectiveness of work in performance assessment, the appropriaindispensable. By therefore, be made software which can take a decision to appraisal. The software is built on the basis of a decision support system whicthe performance of employees by  using methods Multifactor Evaluation PrMultifactor Evaluation Process is a quantitative method that uses weightinis done by providing an intuitive and subjective judgment, weighing the varimportant influence on alternative options. The results of the Multifactor Evaluation Process of this software sform very good, good,  enough, less good and not good. The result of this proceconsideration promotion as well as year-end bonuses based on their perform Keywords—Decision Support System, Multifactor Evaluation Process